Improving Students' Reading Comprehension Ability and Learning Activeness Using Project-Based Learning Model Assisted by Visual Media - Rahayu , Kadek Galuh Andriasih; Ardana, I Made; Suarni, Ni Ketut (Jurnal Pedagogi dan Pembelajaran, 2024)
The low ability of students to understand reading and the low level of student activity in the learning process is influenced by a lack of design innovation, learning processes, and a lack of strengthening literacy for students. This research aims to analyze the project-based learning model assisted by visual media on the reading comprehension ability and active learning of Indonesian language students in grade II elementary school.. This pseudo-experimental research is designed by a single factor independent group design. The population in this study was 297 students with a total of 62 students as a sample determined by random sampling technique. Data were collected by tests of reading comprehension and observation of student learning activity. Then, the data was analyzed using the MANOVA technique. The results showed that there were differences in reading comprehension and learning activity simultaneously among students who participated in the project based learning model assisted by visual media with conventional learning. This means that the project based learning model with the novelty of visual media has an effect on reading comprehension and active learning of second grade elementary school students. The research results can be used as a reference in making learning designs more innovative.